Pengaruh Etos Kerja Dan Beban Kerja Terhadap Kinerja Karyawan Pada PT. Graha Menara Hijau Jakarta Selatan - Guntur Pratama Wildantiarno; Ma'fiyah Ma'fiyah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the partial and simultaneous influence of Work Ethic and Workload on Employee Performance at PT. Graha Menara Hijau, South Jakarta. The population consists of 95 employees, and the sample was selected using a saturated sampling technique, involving all 95 employees of PT. Graha Menara Hijau. This research uses a quantitative approach. The analytical methods used include calculating the results of each variable, descriptive tests, classical assumption tests, multiple linear regression, the coefficient of determination test, and hypothesis testing. The t-test results show that Work Ethic has a significance value of 0.007 < 0.05 and a t-count of 5.833 > t-table of 0.67708, which means that Work Ethic partially influences Employee Performance. The t-test results also show that Workload has a significance value of 0.000 < 0.05 and a t-count of 5.695 > t-table of 0.67708, which means that Workload partially influences Employee Performance. The F-test results indicate a significance value of 0.000 < 0.05 and an F-count of 16.822 > F-table of 3.94, indicating that Work Ethic and Workload simultaneously influence Employee Performance. The results of the Coefficient of Determination (R²) test show an Adjusted R-Square of 0.852, which means that Work Ethic and Workload simultaneously contribute 85.2% to Employee Performance, while the remaining 14.8% is influenced by other variables not examined in this study